2016
DOI: 10.1007/s40122-016-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib Possesses Anxiolytic Properties in Patients Undergoing Total Knee Arthroplasty: A Prospective, Randomized, Double-Blind, Placebo-Controlled, Clinical Study

Abstract: Introduction Intravenous administration of parecoxib could provide significant pain relief in surgical operations that require additional forms of analgesia. However, very little is known about its effects on the anxiety levels of patients before a surgical procedure. The aim of this prospective study was to investigate whether intravenous parecoxib, pre-emptively administered, has an effect on anxiety levels experienced post-surgically after total knee arthroplasty (TKA) and if it influences the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…Our finding is in accordance with previous observations that cyclooxygenase-2 inhibition reduces anxiety-like behavior [ 10 12 ]. The specific mechanism through which chronic parecoxib administration exerts an anxiolytic-like effect remains unclear.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding is in accordance with previous observations that cyclooxygenase-2 inhibition reduces anxiety-like behavior [ 10 12 ]. The specific mechanism through which chronic parecoxib administration exerts an anxiolytic-like effect remains unclear.…”
Section: Discussionsupporting
confidence: 94%
“…cyclooxygenase-2 inhibitors improve stress-induced anxiety-like behavior in mice [ 11 ]. A clinical study showed that preventative administration of cyclooxygenase-2 inhibitor parecoxib exerts anxiolytic effects in patients undergoing total knee arthroplasty [ 12 ]. However, comparatively few studies have investigated the effects of cyclooxygenase-2 inhibitors on anxiety-like behavior under normal physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Parecoxib has been demonstrated as effective in several models of postoperative pain 38 with no effect on platelet function or gastric mucosa at doses up to 40 mg two times a day. 39 Some recent literature 40 41 also revealed that 40 mg of intravenous administered parecoxib can alleviate the anxiety during the perioperative period of TKA, which consequently led to better satisfaction scores and overall experiences for the patients. Celecoxib, another oral specific COX-2 inhibitor, was shown as having short-term pain reduction and morphine sparing effect in patients undergoing TKA, 13 as well as improving functionality recovery if prolonged use up to 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Such an adverse event, which is of concern for physicians and physiotherapists, can be avoided by modifying the concentration of the administered local anesthetic or by selecting alternative peripheral blocks, such as adductor canal block (ACB), even if the CFNB has resulted in being more efficacious in this population [ 17 ]. In addition, local anesthetics infiltration (LAI) in the knee joint by the orthopedic surgeon, which is becoming very popular, is successful and nowadays frequently utilized, while patient-controlled analgesia with intravenous morphine is also successful in postoperative analgesia [ 21 ]. Nevertheless, its use is hindered by opioid adverse effects, such as nausea, vomiting, dizziness, increased percentages of postoperative delirium, and the risk of respiratory depression, often resulting in its withdrawal in certain patients’ categories [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, local anesthetics infiltration (LAI) in the knee joint by the orthopedic surgeon, which is becoming very popular, is successful and nowadays frequently utilized, while patient-controlled analgesia with intravenous morphine is also successful in postoperative analgesia [ 21 ]. Nevertheless, its use is hindered by opioid adverse effects, such as nausea, vomiting, dizziness, increased percentages of postoperative delirium, and the risk of respiratory depression, often resulting in its withdrawal in certain patients’ categories [ 21 ]. Our protocol incorporated CFNB in all patients and on-demand PCA with morphine, while randomization was based on parecoxib administration.…”
Section: Discussionmentioning
confidence: 99%